Cardiohemodynamic and heart rate variability changes observed in the North newcomer Caucasians and people born to them in the 1st - 2nd generations at active orthostatic test exposure - I. V. Averyanova; A. L. Maksimov (Сибирский научный медицинский журнал, 2021)
Objective: to specify changes in functional reserves of hemodynamics and heart rate variability at performing active orthostatic test by migrants (0-th generation) and those born in the North in the 1st and 2nd generation, all residents of Magadan region.Material and methods: 106 young males aged 17-21, permanently residing in the North, were examined. All the young men were divided into 3 groups: newcomer Caucasians (0-th generation) and people born to them in the region (in the 1st and 2nd generations). Readjustments in cardiorhythm and hemodynamics in response to the active orthostatic test were studied.Results. At the resting state, young male examinees demonstrated their parasympathetic influence of the autonomic system on the heart rate regulation to increase from the 0th to the 2nd generation, which is observed together with more economical functioning of the cardiovascular system. In response to the orthostatic test, the 2nd generation subjects showed optimum autonomic support in hemodynamics by reducing the activity of the parasympathetic link which reflected the inhibition of vagal activity in order to moderately activate the sympathetic link of autonomic regulation.Conclusion. We could observe optimization in cardiovascular system in each next generation in the North with the decrease in reactivity to active orthostatic test and the growth in the parasympathetic link of autonomic nervous system at rest.